Experiment Analysis and Baseline Hydraulic Characterisation of HiPOR, a High Pressure Crude Oil Fouling Rig - Z. Tajudin; J. Martinez Minuesa; E. Diaz-Bejarano; I. Valkov; P. Orzlowski; F. Coletti; S. Macchietto; G.F. Hewitt (Chemical Engineering Transactions, 2015)
Crude oil fouling is one of the most common and challenging issue in refinery heat exchangers. It not only affects continuity and safety of operations but it also costs to a refinery several millions a year in maintenance, extra fuel and loss of production. To improve the understanding of fouling high quality primary measurements are needed at temperatures, pressures and flow conditions close to those in actual refining operations. To produce such critical data a high pressure oil rig (HiPOR) was developed at Imperial College London and licensed to Hexxcell Ltd. In parallel, a mathematical model for the rig has been developed. The model includes all the major equipment components in the process flow diagram and is capable of simulating the operations of HiPOR including start-up, heating and cooling. In this paper, the measurements obtained from a set of experimental runs with a non-fouling oil and in cold conditions (i.e. at oil constant temperatures below 100 °C) are used to characterize the hydraulic performance of the rig. A baseline validation of the hydraulic performance of the model against those data is also presented. Excellent reproducibility of all primary measurements at various operating conditions was demonstrated across repeated runs, providing excellent confidence on the reliability of the data for following analyses. The simulation results also show good agreement of the model with the experimental hydraulic data.